Question
upstudy study bank question image url

Question 1 1.1. Prove that the sum of \( n \) terms of an arithmetic sequence of \( n \) terms is given formula: \( S_{n}=\frac{n}{2}[2 a+(n-1) d] \) 1.2. Consider the series: \( 5+8+11+14+17+\ldots+302 \) 1.2.1. Determine the formula for the \( n^{t h} \) term of the series. 1.2.2. How may terms are there in the series? 1.2.3. Express the series in sigma notation. 1.2.4. Determine the sum of the terms in the series. 1.3. Determine the value of \( n \) if 1.4. Expand and evaluate: \( \sum_{k=1}^{n}(3 k-15)=285 \)

Ask by Olson Ortiz. in South Africa
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

- **1.1** Proven the formula \( S_n = \frac{n}{2}[2a + (n-1)d] \) for the sum of an arithmetic sequence. - **1.2.1** The \( n^{th} \) term is \( a_n = 3n + 2 \). - **1.2.2** There are 100 terms in the series. - **1.2.3** The series in sigma notation is \( \sum_{n=1}^{100} (3n + 2) \). - **1.2.4** The sum of the series is 15,350. - **1.4** The value of \( n \) is 19.

Solution

Let's solve the problem step by step. ### 1.1 Prove the formula for the sum of \( n \) terms of an arithmetic sequence An arithmetic sequence is defined by its first term \( a \) and a common difference \( d \). The \( n \)-th term of the sequence can be expressed as: \[ a_n = a + (n-1)d \] The sum of the first \( n \) terms \( S_n \) can be calculated as follows: 1. Write the sum in two different orders: \[ S_n = a + (a + d) + (a + 2d) + \ldots + (a + (n-1)d) \] \[ S_n = (a + (n-1)d) + (a + (n-2)d) + \ldots + a \] 2. Add these two equations: \[ 2S_n = [2a + (n-1)d] + [2a + (n-1)d] + \ldots + [2a + (n-1)d] \] There are \( n \) terms of \( [2a + (n-1)d] \). 3. Therefore, we have: \[ 2S_n = n[2a + (n-1)d] \] 4. Dividing both sides by 2 gives: \[ S_n = \frac{n}{2}[2a + (n-1)d] \] This proves the formula for the sum of the first \( n \) terms of an arithmetic sequence. ### 1.2 Consider the series: \( 5 + 8 + 11 + 14 + 17 + \ldots + 302 \) #### 1.2.1 Determine the formula for the \( n^{th} \) term of the series. The first term \( a = 5 \) and the common difference \( d = 3 \). The \( n^{th} \) term can be expressed as: \[ a_n = a + (n-1)d = 5 + (n-1) \cdot 3 = 3n + 2 \] #### 1.2.2 How many terms are there in the series? To find the number of terms, set the \( n^{th} \) term equal to 302: \[ 3n + 2 = 302 \] Solving for \( n \): \[ 3n = 300 \\ n = 100 \] #### 1.2.3 Express the series in sigma notation. The series can be expressed in sigma notation as: \[ \sum_{n=1}^{100} (3n + 2) \] #### 1.2.4 Determine the sum of the terms in the series. Using the sum formula \( S_n = \frac{n}{2}[2a + (n-1)d] \): - \( n = 100 \) - \( a = 5 \) - \( d = 3 \) Calculating the sum: \[ S_{100} = \frac{100}{2}[2 \cdot 5 + (100-1) \cdot 3] \\ = 50[10 + 297] \\ = 50 \cdot 307 \\ = 15350 \] ### 1.3 Determine the value of \( n \) if It seems like the question is incomplete. Please provide the complete statement for part 1.3. ### 1.4 Expand and evaluate: \[ \sum_{k=1}^{n}(3k - 15) = 285 \] This can be split into two separate sums: \[ \sum_{k=1}^{n}(3k) - \sum_{k=1}^{n}(15) = 285 \] Calculating each part: 1. The first sum: \[ \sum_{k=1}^{n}(3k) = 3\sum_{k=1}^{n}k = 3 \cdot \frac{n(n+1)}{2} = \frac{3n(n+1)}{2} \] 2. The second sum: \[ \sum_{k=1}^{n}(15) = 15n \] Putting it all together: \[ \frac{3n(n+1)}{2} - 15n = 285 \] Multiplying through by 2 to eliminate the fraction: \[ 3n(n+1) - 30n = 570 \\ 3n^2 + 3n - 30n - 570 = 0 \\ 3n^2 - 27n - 570 = 0 \] Dividing the entire equation by 3: \[ n^2 - 9n - 190 = 0 \] Now, we can solve this quadratic equation using the quadratic formula: \[ n = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} = \frac{9 \pm \sqrt{(-9)^2 - 4 \cdot 1 \cdot (-190)}}{2 \cdot 1} \] Calculating the discriminant: \[ = \frac{9 \pm \sqrt{81 + 760}}{2} = \frac{9 \pm \sqrt{841}}{2} = \frac{9 \pm 29}{2} \] Calculating the two possible values for \( n \): 1. \( n = \frac{38}{2} = 19 \) 2. \( n = \frac{-20}{2} = -10 \) (not valid since \( n \) must be positive) Thus, the value of \( n \) is: \[ n = 19 \] ### Summary of Results: - 1.1: Proven the formula for \( S_n \). - 1.2.1: \( a_n = 3n + 2 \) - 1.2.2: \( n = 100 \) - 1.2.3: \( \sum_{n=1}^{100} (3n + 2) \) - 1.2.4: \( S_{100} = 15350 \) - 1.4: \( n = 19 \)

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To understand an arithmetic sequence, think of it as a straight road where you are moving at a constant speed. Each term is a landmark you pass by, and the common difference \(d\) is how far apart those landmarks are. The formula for the sum of the first \(n\) terms gives you the distance traveled when you know your starting point \(a\) and your speed \(d\}. This way, you can easily calculate how far you've gone without adding up each term individually! When it comes to real-world applications, think about how arithmetic sequences pop up in everyday life, like when calculating expenses or budgeting. For example, if you save a fixed amount of money each week, the total savings after a certain number of weeks would form an arithmetic series. Whether you're planning a road trip, investing in a savings plan, or even organizing events, understanding how to sum these sequences can help you make smarter decisions!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy